Development of Local History Digital Book Teaching Materials At SMA 13 Jambi City - Febriani, Meli; Sunardi, Sunardi; Pelu, Musa (International Journal of Educational Research & Social Sciences, 2022)
This study aims to determine students' needs for digital-based learning media. The research method used in this research is through research and development, with the ADDIE development model. Sources and methods of data collection were collected from document studies such as from libraries, internet, scientific articles, books, journals and documents related to research themes, then field observations. The results of the research, these writings serve as reading values and recommendations for the development of local historical awareness in Indonesia, especially in Jambi City. The exploration of this research tries to reveal the application of digital books as a medium in learning in schools.